Fumed silica powder with reduced silanol group density
Patent Information
- Application Number
- JP2023546241
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-02-11
- Filing Date
- 2022-01-19
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2042-01-19
AI Technical Summary
Existing methods struggle to produce fumed silica powder with reduced silanol group density while maintaining a small particle size and narrow particle size distribution, leading to issues with dispersibility and viscosity in compositions, and high water content, which is undesirable for applications like lithium-ion batteries.
A method involving heat treatment of untreated fumed silica powder at controlled temperatures and durations, typically between 350°C to 1,250°C, while in motion, to reduce silanol groups by 15% to 70% without significantly altering the BET surface area, combined with optional surface treatment using organosilanes or silazanes to achieve low water content and improved dispersibility.
The method produces fumed silica powder with low silanol group density, low water content, and narrow particle size distribution, ensuring good dispersibility and minimal viscosity increase in compositions, suitable for applications requiring low tamping density and hydrophobicity.
Abstract
Description
[Technical field]
[0001] The present invention relates to a fumed silica powder having a relatively small particle size and reduced silanol group density, a method for its preparation and its use. [Background technology]
[0002] Silica powder, especially fumed silica powder, is a very useful additive for a variety of applications. To name just a few of these applications, silica can be used as a rheology modifier or anti-settling agent in paints, coatings, silicones and other liquid systems. Silica powder can improve powder flowability, optimize the mechanical or optical properties of silicone compositions, and can also be used as a filler for pharmaceuticals or cosmetics, adhesives or sealants, toners, and other compositions.
[0003] One of the important properties of silica materials that determines their suitability for a particular application is related to the silanol group density, i.e. the amount of free silanol groups (SiOH) relative to the surface area of the silica. Untreated silica is hydrophilic due to the presence of polar silanol groups on its surface. The silanol groups on the surface of the silica can form hydrogen bonds with each other or with binders that contain hydroxy groups, e.g., terminal dihydroxypolydimethylsiloxane. As a result of these filler-polymer interactions, formulations containing silica can have undesirably high viscosities and altered glass transition temperatures and crystallization behavior.
[0004] On the other hand, fumed silica with a high silanol group density tends to absorb a significant amount of water, leading to an increased water content of such silica. However, in some applications, such as additives in lithium-ion battery components (e.g., separators, electrodes, electrolytes), the presence of water is undesirable. Therefore, Korean Patent Application Publication No. 20150099648 discloses a separator membrane coated with vinyl-modified silica particles that can be used in lithium-ion batteries with gel polymer electrolytes. The water contained in such silica additives can cause some water-sensitive components in lithium-ion batteries, such as LiPF 6 It will react with LiPF 6 is often present in electrolytes and can cause the electrolyte to decompose, releasing reactive species such as HF, which contribute to the deactivation of the battery. Therefore, silicas with reduced silanol density may be necessary or useful for applications involving water-sensitive components.
[0005] Description of the Prior Art Approximately 2-15 SiOH / nm2 per surface area, depending on the nature of the hydrophilic silica 2 A silanol group density of 100% is observed.
[0006] A typical attempt to reduce the silanol group density of silica is to at least partially cover the free silanol groups with organosilane groups. Thus, in EP 1 433 749 A1, it is described that the particle surface nm 2 The preparation of partially hydrophobic silica with a silanol group density of 0.9 to 1.7 SiOH per square meter has been described. The preparation of such partially hydrophobic particles has been demonstrated to have a BET surface area of 100 m. 2 This is done by using a 0.015 to 0.15 mmol reduction in the amount of silane per g of silica.
[0007] German Patent No. 2123233 describes the particle surface nm 2 1.18SiOH / nm 2 This application describes a method for preparing micronized silicon dioxide having a silanol group density of greater than 1.
[0008] German Patent Specification No. 1767226 discloses a method for producing finely divided silica by heating pyrogenic silica in a fluidized bed.
[0009] It is less common to intentionally reduce the silanol group density of hydrophilic silica.
[0010] One common method is described in US Pat. No. 4,664,679, which discloses the surface treatment of silicic anhydride by reacting the silanol groups with various coupling agents.
[0011] US Patent Application Publication No. 2016 / 0355685 discloses a method for hydrolyzing tetramethoxysilane, then drying and calcining the resulting product in an electric furnace at 1,050°C for 1 hour to obtain a 2 to 35 m 2 We describe a method for preparing silica with a relatively low BET surface area of 100 nm / g by the sol-gel method, milling the resulting coarse particles, and hydrophobizing them with silane.
[0012] U.S. Patent No. 2,866,716 discloses a method for modifying the surface of a colloidal silica substrate with free silanol groups, which comprises heating the silica substrate at a temperature between 300 and 700° C. until the specific surface area is reduced to less than 85% of its initial value. However, the silanol group density of the heat-treated silica is approximately 2 OH / nm 2 That's all.
[0013] EP 1 860 066 A1 describes a silanol group density of about 2.7 OH / nm 2 with a typical residual moisture content of 3.5 wt. % which is prepared by spray drying precipitated silica followed by heating at 450° C. in a fluidized bed reactor and grinding. 2 describes the preparation of precipitated silica,
[0014] Both precipitated and colloidal silicas are usually prepared in aqueous media, so they have a relatively high water content and often a high silanol group density. These types of silica are not as suitable for preparing silica with a low silica group density as fumed silica. Due to the high temperature of the preparation process, the silanol group density of fumed silica is usually 2.2-3.0 SiOH / nm 2 and fumed silica is a better precursor to silica with reduced silanol group density.
[0015] The silanol group density of fumed silica can be reliably measured by methods such as the reaction of silica with lithium aluminum hydride, as described in Journal of Colloid and Interface Science, Vol. 125, No. 1 (1988), pp. 61-68. A typical hydrophilic silica (Aerosil® OX 50, BET=50m 2 / g, Aerosil® 130, BET=129m 2 / g, Aerosil® 150, BET=155m 2 / g, Aerosil® 200, BET=196m 2 / g, Aerosil® 300, BET=303m 2 / g, Aerosil® 380, BET=372m 2 / g) and surface-treated (hydrophobic) silica (Aerosil® R972, BET=102m 2 / g, Aerosil® R812, BET=245m 2 / g) were analyzed using this method, which yields approximately 2.0-2.5 OH / nm for typical hydrophilic silica. 2 , and 0.53 to 0.54 OH / nm for hydrophobic silica 2 A typical silanol group density of 0.01 was shown.
[0016] From US Pat. No. 3,873,337 it is known to treat fumed silica in a fluidized bed with a dry inert gas flow at 700-1,000 ° C for 1-60 seconds before hydrophobization with dimethyldichlorosilane to remove physically bound water. Due to the very short drying time, this step can only remove weakly bound water, leaving the silanol groups of the silica unaffected. In fact, in this method, to achieve extensive hydrophobization with dimethyldichlorosilane, it is desirable for the silanol group density of the hydrophilic precursor to be the maximum possible. Therefore, US Pat. No. 3,873,337 does not disclose the preparation of hydrophilic silica powders with reduced silanol group density.
[0017] JP 2014-055072 A describes a method for producing a 50 to 400 m 2 / g and a BET surface area of approximately 2.5 OH / nm 2 This paper describes the preparation of amorphous silica having a silanol group density of 0.55 to 2.09 g / cm. Such silica powder is mixed with a binder and a solvent, and heated at 100 to 500°C in an oxygen-containing gas atmosphere to form a molded product such as granules. The molded product thus obtained is fired at 600 to 1,200°C for 30 minutes to 24 hours to obtain a silanol group density of 0.55 to 2.09 g / cm. 3 Mechanically stable sintered bodies in the mm size range are obtained with densities in the range of 100 to 1500 nm. JP 2014-055072 does not disclose the preparation of any silica powder.
[0018] It is well known from the prior art to obtain sintered shaped bodies by heat treatment of compacted silica granules or fragments. Thus, WO 2009 / 007180 discloses a method for the preparation of silica glass granules, in which fumed silica powder is compressed into small chunks (slugs) and then crushed into fragments with a particle size of 100-800 μm and a tamping density of 300-600 g / L. The latter are heated at 600-1,100 ° C in an atmosphere suitable for the removal of hydroxyl groups and further sintered at 1,200-1,400 ° C. Powders with small particle sizes are not disclosed in this patent application. [Prior art documents] [Patent documents]
[0019] [Patent Document 1] Korean Patent Application Publication No. 20150099648 [Patent Document 2] European Patent Application Publication No. 1433749 [Patent Document 3] German Patent No. 2123233 [Patent Document 4] German Patent No. 1767226 [Patent Document 5] U.S. Pat. No. 4,664,679 [Patent Document 6] US Patent Application Publication No. 2016 / 0355685 [Patent Document 7] U.S. Patent No. 2,866,716 [Patent Document 8] European Patent Application Publication No. 1860066 [Patent Document 9] U.S. Pat. No. 3,873,337 [Patent Document 10] JP 2014-055072 A [Patent Document 11] International Publication No. 2009 / 007180 Brochure [Non-patent literature]
[0020] [Non-Patent Document 1] Journal of Colloid and Interface Science, Vol. 125, No. 1 (1988), pp. 61-68 Summary of the Invention [Problem to be solved by the invention]
[0021] Challenges and Solutions Good dispersibility and thixotropic properties of fumed silica fillers in various compositions, for example in silicone or starch compositions, are very important for many applications. Dispersibility is mainly related to the size of the silica particles and their strong and weak aggregation in the composition. The thixotropic properties of silica depend on the strong and weak aggregation of silica, as well as the density of silanol groups. As is known from the prior art, the reduction of the silanol group content by heat treatment is often closely related to a significant reduction in the BET surface area and weak aggregation of the particles. It is therefore difficult to significantly reduce the silanol group density of hydrophilic silica, while at the same time keeping the BET surface area unchanged, keeping the silica particles small and their particle size distribution narrow. It is therefore very challenging to simultaneously achieve good dispersibility of fumed silica fillers and low viscosity increase (thickening effect) in compositions filled with such silica.
[0022] On the other hand, the water content of both hydrophilic and surface-treated silicas, especially hydrophobic fumed silica, needs to be reduced for use in water-sensitive applications, such as lithium-ion batteries.
[0023] Therefore, the technical problem to be solved by the present invention is to provide a fumed silica powder that has high dispersibility, causes little increase in viscosity in a composition, and has a low water content, and a method suitable for efficiently producing such a silica powder. [Means for solving the problem]
[0024] The present invention relates to BET surface area d measured by reaction with lithium aluminum hydride SiOH The number of silanol groups on the 2 and the particle size d measured by static light scattering (SLS) in a 5 wt % aqueous dispersion of silica after 120 s of ultrasonic treatment at 25 °C. 95A step (A) of subjecting a surface-untreated fumed silica powder having a particle size of 10 μm or less to a heat treatment at 350° C. to 1,250° C. for 5 minutes to 5 hours. A method for producing a fumed silica powder comprising: The temperature and duration of the heat treatment are SiOH However, the d of the untreated silica used SiOH was selected to reduce by 15% to 70%. The heat treatment is carried out while the fumed silica powder is in motion. This provides:
[0025] Surprisingly, it has been found that the method of the present invention allows the preparation of fumed silica powders with a particularly low water content, while keeping the agglomerate particle size at a very small level, i.e., while keeping the heat-treated silica particles in a state in which they can be well dispersed in various compositions. Moreover, this method allows the production of heat-treated fumed silica particles with a relatively narrow particle size distribution. The material obtained, like its starting material, is characterized by a low tamping density. This fact allows the use of such heat-treated material in all fields of application in which a fumed silica with a low tamping density is particularly required, for example as a filler or flow improver.
[0026] Method for producing silica powder The surface-untreated silica used in step (A) of the method The term "powder" in the context of this specification refers to fine particles, i.e. particles having a mean particle size of typically d 50 The particle size includes particles smaller than 50 μm, preferably smaller than 10 μm. The term "surface untreated" in the context of this specification relates to hydrophilic silica that has not been surface modified by treatment with any surface treatment agent. Such surface untreated silicas have a low carbon content, usually less than 1% by weight, more preferably less than 0.5% by weight, as determined by elemental analysis according to EN ISO 3262-20:2000 (chapter 8). The sample to be analyzed is weighed into a ceramic crucible, a combustion additive is added and the sample is heated in an induction furnace under a flow of oxygen. The carbon present is oxidized to CO 2 CO 2 The amount of gas is quantified by an infrared detector. The carbon content stated refers to all carbon-containing components of the silica, excluding compounds that are non-flammable under the test conditions (e.g., silicon carbide, etc.). The methanol wettability of such surface untreated fumed silica is typically less than 20% by volume of methanol in a methanol / water mixture, preferably less than 10% by volume, more preferably less than 5% by volume, and more preferably about 0% by volume. The degree of hydrophilicity of a silica powder can be measured by its methanol wettability, as described in detail, for example, on pages 5-6 of WO 2011 / 076518. In pure methanol, the hydrophilic silica powder separates completely from the methanol without being wetted by the solvent. In contrast, in pure water, the hydrophilic silica disperses throughout the solvent (complete wetting occurs). During the measurement of the methanol wettability of a hydrophilic silica powder, the tested silica sample is mixed with various methanol / water mixtures and the maximum methanol content is measured when the silica is not separated, i.e., 100% of the silica used remains well dispersed in the test mixture. This methanol content (volume %) in the methanol / water mixture is called the methanol wettability. The lower the methanol wettability, the more hydrophilic the silica powder tested is.
[0027] The fumed surface-untreated silica used in step (A) of the process of the present invention preferably has a BET surface area d SiOH The number of silanol groups per nm is at least 1.3SiOH / nm 2 , more preferably at least 1.4 SiOH / nm 2 , more preferably at least 1.5 SiOH / nm2 , more preferably 1.5 to 3.0SiOH / nm 2 It is.
[0028] Number of silanol groups per BET surface area d SiOH (also called silanol group density, nm 2 The surface area (expressed as the number of SiOH groups per unit area) can be determined by the method detailed in EP 0 725 037, p. 8, line 17 to p. 9, line 12, by reaction of silica powder with lithium aluminum hydride. This method is also described in the Journal of Colloid and Interface Science, Vol. 2, No. 1 (1988), pp. 61-68.
[0029] The silanol (SiOH) groups of silica are converted to lithium aluminum hydride (LiAlH 4 ) is reacted with silanol groups, and the amount of gaseous hydrogen produced during this reaction is the amount of silanol groups in the sample, n SiOH (in mmole SiOH / g) is measured. The corresponding BET surface area (m 2 / g) to calculate the silanol content in mmol SiOH / g as the number of silanol groups per BET surface area, d SiOH can be easily converted to: d SiOH [SiOH / nm2] = (n SiOH [mmol SiOH / g] x N A ) / (BET[m 2 / g]×10 21 ) In the formula, N A is Avogadro's constant (~6.022*10 23 ).
[0030] The fumed surface-untreated silica used in step (A) of the method of the present invention is 20 ml 2 / g, preferably 20m 2 / g~600m 2 / g, more preferably 30m 2 / g~500m 2 / g, more preferably 40m 2 / g~400m 2 The specific surface area, also referred to simply as the BET surface area, can be determined by nitrogen adsorption according to the Brunauer-Emmett-Teller method in accordance with DIN 9277:2014.
[0031] The term "silica" in the context of this specification refers to the individual compounds (silicon dioxide, SiO 2 ), silica-based mixed oxides, silica-based doped oxides, or mixtures thereof. By "silica-based" it is meant that the corresponding silica material comprises at least 70% by weight, preferably at least 80% by weight, more preferably at least 90% by weight, more preferably at least 95% by weight, and most preferably at least 98% by weight of silicon dioxide.
[0032] "Fumed" silicas, also known as "pyrogenic" or "pyrogenically produced" silicas, are prepared by pyrolytic processes such as flame hydrolysis or flame oxidation. This involves the oxidation or hydrolysis of hydrolytic or oxidative starting materials, generally in a hydrogen / oxygen flame. Starting materials used for pyrolytic processes include organic and inorganic substances. Silicon tetrachloride is particularly suitable. The hydrophilic silicas thus obtained are amorphous. Fumed silicas are usually in an aggregated form. "Agglomerated" means that the so-called primary particles that are initially formed during production are firmly bonded to each other in a subsequent reaction to form a three-dimensional network. The primary particles are substantially free of pores and have free hydroxyl groups on the surface. If necessary, such hydrophilic silicas can be hydrophobized, for example by treatment with reactive silanes.
[0033] At least two different metal sources in the form of volatile metal compounds, e.g., chlorides, are added to the H 2 / O 2It is known to produce pyrogenic mixed oxides by reacting them simultaneously in a flame. All components of the mixed oxide thus prepared are generally distributed homogeneously throughout the mixed oxide material, in contrast to other types of materials such as mechanical mixtures of several metal oxides, doped metal oxides, etc. In the latter case, for example in the case of a mixture of several metal oxides, there may be separate regions of corresponding pure oxides, which determine the properties of such mixtures.
[0034] The surface-untreated fumed silica powder used in the method of the present invention has an average primary particle size d of 5 nm to 50 nm, preferably 5 nm to 40 nm. 50 The average size of the primary particles d 50 can be measured by transmission electron microscopy (TEM) analysis. 50 To calculate a representative average value, at least 100 particles need to be analyzed.
[0035] The surface-untreated fumed silica powder used in the process of the present invention has a particle size d of 10 μm or less, preferably 5 μm or less, more preferably 3 μm or less, more preferably 2 μm or less, preferably 1 μm or less, as measured by static light scattering (SLS) after ultrasonic treatment of a 5 wt % aqueous dispersion of silica at 25° C. for 120 seconds. 90 The resulting measured particle size distribution reflects the particle size not exceeded by 90% of all particles, d 90 The above particle size d is used to define 90 refers to the particle size of strongly and weakly agglomerated fumed silica particles.
[0036] The surface-untreated fumed silica powder used in the method of the present invention preferably has a relatively narrow particle size distribution, which has a particle size distribution span (d 90 ~d 10 ) / d 50 can be characterized by the value of
[0037] The surface-untreated fumed silica powder used in the method of the present invention preferably has a tamped density of 300 g / L or less, more preferably 250 g / L or less, more preferably 20 g / L to 250 g / L, more preferably 20 g / L to 200 g / L, more preferably 25 g / L to 180 g / L, more preferably 30 g / L to 150 g / L. The tamped density (also called "tap density") of various powders or coarse granular materials can be measured according to DIN ISO 787-11:1995 "General test methods for pigments and extenders - Part 11: Determination of tamped volume and apparent density after tamping". This includes measuring the apparent density of the bed after stirring and tamping.
[0038] The surface-untreated fumed silica powder used in the method of the present invention preferably has a water content of 3% by weight or less, more preferably 2% by weight or less, more preferably 1.5% by weight or less, more preferably 1.2% by weight or less, as measured by Karl Fischer titration, which may be performed using any suitable Karl Fischer titration apparatus, for example a Karl Fischer titration apparatus conforming to STN ISO 760.
[0039] Heat Treatment The heat treatment of the surface-untreated fumed silica powder in the method of the present invention is carried out at a temperature of 350° C. to 1,250° C., preferably 400° C. to 1,250° C., more preferably 400° C. to 1,200° C., more preferably 500° C. to 1,200° C., more preferably 700° C. to 1,200° C., more preferably 1,000° C. to 1,200° C. The duration of this heat treatment depends on the applied temperature and is generally 5 minutes to 5 hours, preferably 10 minutes to 4 hours, more preferably 20 minutes to 3 hours, and even more preferably 30 minutes to 2 hours.
[0040] It has been observed that the duration of the heat treatment step can have a significant effect on the properties of the resulting fumed silica powder. Thus, if the duration of the heat treatment step, carried out at 350-1,250 °C, is less than 5 minutes, a significant decrease in the water content of the silica is usually not observed, especially if the starting material for the heat treatment has been predried before the heat treatment and is not wet itself, e.g., if the water content is less than 3% by weight as measured by Karl Fischer titration. Conversely, if the duration of the heat treatment step exceeds 5 hours, it usually does not bring about any further significant changes in the water content of the resulting silica, but the particle size of the resulting particles may increase.
[0041] The heat treatment in the process of the present invention clearly reduces the number of free silanol groups by condensation of the free silanol groups and formation of O-Si-O bridges.
[0042] The temperature and duration of the heat treatment step are determined by the d SiOH However, the d of the thermally untreated and surface untreated fumed silica powder used SiOH Therefore, the fumed silica powder prepared by the method of the present invention has a BET surface area d SiOH 1.55SiOH / nm 2 Less than 0.6SiOH / nm 2 ~1.55SiOH / nm 2 , more preferably 0.6SiOH / nm 2 ~1.5SiOH / nm 2 , more preferably 0.6SiOH / nm 2 ~1.4SiOH / nm 2 , more preferably 0.6SiOH / nm 2 ~1.3SiOH / nm 2 , more preferably 0.6SiOH / nm 2 ~1.2SiOH / nm 2 , more preferably 0.7SiOH / nm 2 ~1.2SiOH / nm 2 , more preferably 0.8SiOH / nm 2 ~1.2SiOH / nm2 , more preferably 0.9SiOH / nm 2 ~1.2SiOH / nm 2 The number of silanol groups is
[0043] The d of the silica used in step (A) of the process of the present invention SIOH It has been found that a reduction in silanol density of less than 10% from the original value is not associated with a substantial reduction in the water content of the silica or other beneficial effects, whereas a reduction in silanol group density of 70% or more is only possible with the simultaneous formation of larger sintered aggregates, which cannot be easily destroyed, for example, by ultrasonication.
[0044] Importantly, in contrast to the silanol density, the BET surface area of the heat-treated silica typically changes only to a relatively small extent during step (A) of the method of the present invention. Thus, during heat treatment, it is preferred that the BET surface area of the fumed silica powder is reduced by at most 50%, more preferably at most 45%, more preferably at most 40%, more preferably at most 35% relative to the BET surface area of the heat-untreated and surface-untreated silica used in step (A) of the method of the present invention.
[0045] The heat treatment in the process of the present invention can be carried out discontinuously (batchwise), semi-continuously or, preferably, continuously.
[0046] The "duration of heat treatment" for a discontinuous process is defined as the total time that the surface-treated fumed silica is heated at a specified temperature. For semi-continuous or continuous processes, the "duration of heat treatment" corresponds to the average residence time of the surface-treated fumed silica powder at the specified heat treatment temperature.
[0047] The method of the present invention is preferably carried out continuously so that the average residence time of the surface-untreated fumed silica powder in the heat treatment step (A) is from 10 minutes to 3 hours.
[0048] In the process of the present invention, the heat treatment is preferably carried out while the fumed silica powder is in motion, preferably in constant motion during the process, i.e. while the silica is in motion during the heat treatment. Such a "dynamic" process is the opposite of a "static" heat treatment process in which the silica particles are not moving, e.g. they are in a bed, e.g. a muffle furnace, during the heat treatment.
[0049] It has been surprisingly found that such a dynamic heat treatment process, in combination with an appropriate temperature and heat treatment duration, allows the production of small particles with a narrow particle size distribution that exhibit particularly good dispersibility in a variety of compositions. In contrast, it has been found that a "static" heat treatment, in which the silica does not move at all, results in sintered aggregates with much larger particle sizes that are much less dispersible in the compositions.
[0050] The process of the present invention can be carried out in any suitable apparatus capable of maintaining the silica powder at the above-specified temperature for the specified time while keeping the silica in motion. Among the suitable apparatus are fluidized bed reactors and rotary kilns. Rotary kilns, especially those with a diameter of 1 cm to 2 m, preferably 5 cm to 1 m, more preferably 10 cm to 50 cm, are preferably used in the process of the present invention.
[0051] Preferably, the silica powder is moved at least temporarily during the heat treatment step (A) at a speed of movement of at least 1 cm / min, more preferably at least 10 cm / min, more preferably at least 25 cm / min, more preferably at least 50 cm / min. Preferably, the silica is moved continuously at this speed for the entire duration of the heat treatment step. The speed of movement in a rotary kiln corresponds to the peripheral speed of this type of reactor. The speed of movement in a fluidized bed reactor corresponds to the flow rate (fluidization velocity) of the carrier gas.
[0052] It is further preferred that substantially no water is added before, during or after carrying out step (A) of the method of the present invention.More preferably, no water is added before, during or after carrying out step (A) of the method of the present invention.In this way, further evaporation of absorbed water can be avoided, and a heat-treated silica powder with a lower water content can be obtained.
[0053] The heat treatment step (A) can be carried out under a flow of gas, for example air or nitrogen, the gas preferably being essentially free of water or having been previously dried.
[0054] "Essentially free of water" means, in relation to a gas, that the humidity of the gas does not exceed the humidity under the conditions of use such as temperature and pressure, i.e. no steam or water vapor is added to the gas prior to use. The water content of the gas used in step (A) of the process of the invention is preferably less than 5% by volume, more preferably less than 3% by volume, more preferably less than 1% by volume, more preferably less than 0.5% by volume.
[0055] Surface Treatment The method for producing the fumed silica powder of the present invention further comprises: Step (B): Surface-treating the fumed silica powder obtained in step (A) with a surface treatment agent selected from the group consisting of organosilanes, silazanes, acyclic polysiloxanes, cyclic polysiloxanes, and mixtures thereof. may include: Preferred organosilanes are, for example, those of the general formulae (Ia) and (Ib): R' x (RO) y Si(C n H 2n+1 ) (Ia) R' x (RO) y Si(C n H 2n-1 ) (Ib) (wherein R=alkyl, e.g. methyl-, ethyl-, n-propyl-, i-propyl-, butyl-, etc.) R'=alkyl or cycloalkyl, such as methyl, ethyl, n-propyl, i-propyl, butyl, cyclohexyl, octyl, hexadecyl, etc. n=1~20 x+y=3 x=0~2, and y=1~3.) It is an alkylorganosilane.
[0056] Among the alkylorganosilanes of formulae (Ia) and (Ib), octyltrimethoxysilane, octyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane are particularly preferred. The organosilanes used for surface treatment may contain halogens such as Cl or Br. The following types of halogenated organosilanes are particularly preferred: - general formula (IIa) and (IIb): X 3 Si(C n H 2n+1 ) (IIa) X 3 Si(C n H 2n-1 ) (IIb) (In the formula, X=Cl, Br, n = 1 to 20.) of organosilanes; - general formula (IIIa) and (IIIb): X 2 (R')Si(C n H 2n+1 ) (IIIa) X 2 (R')Si(C n H 2n-1 ) (IIIb) (In the formula, X=Cl, Br, R'=alkyl, e.g. cycloalkyl such as methyl, ethyl, n-propyl, i-propyl, butyl, cyclohexyl, etc. n = 1 to 20.) of organosilanes; - general formula (IVa) and (IVb): X(R') 2Si(C n H 2n+1 ) (IVa) X(R') 2 Si(C n H 2n-1 ) (IVb) (In the formula, X=Cl, Br, R'=alkyl, e.g. cycloalkyl such as methyl, ethyl, n-propyl, i-propyl, butyl, cyclohexyl, etc. n = 1 to 20.) of organosilanes.
[0057] Of the halogenated organosilanes of formulae (II) to (IV), dimethyldichlorosilane and chlorotrimethylsilane are particularly preferred. The organosilanes used may also contain substituents other than alkyl or halogen substituents, such as fluorine substituents or some other functional groups. Preferably, the organosilanes have the general formula (V): (R' ') x (RO) y Si(CH 2 ) m R' (V) (Wherein R' '=alkyl such as methyl, ethyl, propyl, etc., or halogen such as Cl or Br; R = alkyl, such as methyl, ethyl, or propyl; x+y=3, x=0~2, y=1~3, m=1~20, R' = methyl, aryl (e.g., phenyl or substituted phenyl residues), heteroaryl-C 4 F 9 , OCF 2 -CHF-CF 3 , -C 6 F 13 , -O-CF 2 -CHF 2 , -NH 2 , -N 3 , -SCN, -CH=CH 2 , -NH-CH 2 -CH 2 -NH 2 , -N-(CH2 -CH 2 -NH 2 ) 2 , -OOC(CH 3 )C=CH 2 , -OCH 2 -CH(O)CH 2 , -NH-CO-N-CO-(CH 2 ) 5 , -NH-COO-CH 3 , -NH-COO-CH 2 -CH 3 , -NH-(CH 2 ) 3 Si(OR) 3 , -S x -(CH 2 ) 3 Si(OR) 3 , -SH, -NR 1 R 2 R 3 (In the formula, R 1 = alkyl, aryl; R 2 =H, alkyl, aryl; R 3 =H, alkyl, aryl, benzyl, C 2 H 4 NR 4 R 5 (In the formula, R 4 =H, alkyl and R 5 =H, alkyl. A functionalized organosilane of the formula:
[0058] Among the functionalized organosilanes of formula (V), 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, glycidyloxypropyltrimethoxysilane, glycidyloxypropyltriethoxysilane, aminopropyltriethoxysilane are particularly preferred.
[0059] General formula R'R 2 Si-NH-SiR 2 R'(VI) (In the formula, R=alkyl such as methyl, ethyl, propyl, etc.; R'=alkyl, vinyl.) The most preferred silazane of formula (VI) is hexamethyldisilazane (HMDS).
[0060] Cyclic polysiloxanes such as octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), dodecamethylcyclohexasiloxane (D6), hexamethylcyclotrisiloxane (D6), etc. are also suitable as surface treatment agents. Among the cyclic polysiloxanes, D4 is most preferably used.
[0061] Another useful type of surface treatment agent has the general formula (VII):
[0062] [ka]
[0063] (In the formula, Y=H, CH 3 , C n H 2n+1 (Wherein, n = 1 to 20), Si(CH 3 ) a X b (In the formula, a=2 to 3, b=0 or 1, and a+b=3.) X=H, OH, OCH 3 , C m H 2m+1 (In the formula, m = 1 to 20.) R, R' = C o H 2o+1 (wherein o=1 to 20), aryl such as phenyl and substituted phenyl residues, heteroaryl, (CH 2 ) k -NH 2 (wherein k=1 to 10), H, u=2 to 1,000, preferably u=3 to 100.) The polysiloxane or silicone oil is
[0064] Among the polysiloxanes and silicone oils of formula (VII), polydimethylsiloxanes are most preferably used as surface treatment agents. Such polydimethylsiloxanes usually have a molar mass of 162 g / mol to 7,500 g / mol, a density of 0.76 g / mL to 1.07 g / mL, and a viscosity of 0.6 mPa·s to 1,000,000 mPa·s.
[0065] In step (B) of the method of the present invention, water can be used in addition to the surface treatment agent. The molar ratio of water to the surface treatment agent in step (B) of the method of the present invention is preferably 0.1-100, more preferably 0.5-50, more preferably 1.0-10, more preferably 1.2-9, more preferably 1.5-8, more preferably 2-7.
[0066] However, if it is necessary to obtain a surface-treated silica powder with a low water content, the amount of water used in the process must be minimized, and ideally no water should be added during the method steps. Therefore, it is preferable to add substantially no water before, during or after the implementation of step (B). The term "essentially free of water" in the context of this specification relates to an addition of less than 1% of the fumed silica powder used in step (B), preferably less than 0.5%, more preferably less than 0.1%, more preferably less than 0.01%, and most preferably no water at all.
[0067] The surface treatment agent and optionally water can be used in the process of the present invention in both vapor and liquid form.
[0068] Step (B) of the method according to the invention can be carried out at a temperature between 10°C and 250°C for 1 minute to 24 hours. The time and duration of step (B) can be selected according to the specific requirements regarding the process and / or the targeted silica properties. Thus, the lower the treatment temperature, the longer the hydrophobization time is usually required. In a preferred embodiment of the invention, the hydrophobization of the fumed silica powder is carried out at 10°C to 80°C for 3 hours to 24 hours, preferably 5 hours to 24 hours. In another preferred embodiment of the invention, step (B) of the method is carried out at 90°C to 200°C, preferably 100°C to 180°C, most preferably 120°C to 160°C for 0.5 hours to 10 hours, preferably 1 hour to 8 hours. Step (B) of the method according to the invention can be carried out under a pressure of 0.1 bar to 10 bar, preferably 0.5 bar to 8 bar, more preferably 1 bar to 7 bar, most preferably 1.1 bar to 5 bar. Most preferably, step (B) is carried out in a closed system under the natural vapor pressure of the surface treatment agent used at the reaction temperature.
[0069] In step B) of the method of the present invention, the fumed silica powder subjected to heat treatment in step (A) is sprayed with a liquid surface treatment agent, preferably at ambient temperature (about 25°C), and the mixture is then heat treated at a temperature between 50°C and 400°C for a period of 1 hour to 6 hours.
[0070] Another method of surface treatment in step (B) can be carried out by treating the fumed silica powder that has been subjected to heat treatment in step (A) with a surface treatment agent, the surface treatment agent being in the form of vapor, and then the mixture is heat treated at a temperature of 50°C to 800°C for 0.5 hours to 6 hours.
[0071] The heat treatment after the surface treatment in step (B) can be carried out under a protective gas, for example nitrogen. The surface treatment can be carried out continuously or batchwise in heatable mixers and dryers equipped with spray devices. Suitable devices can be, for example, ploughshare mixers or plates, cyclones, or fluidized bed dryers.
[0072] The amount of the surface treatment agent used varies depending on the type of particles and the type of surface treatment agent applied, but is usually 1% to 25% by weight, preferably 2% to 20% by weight, more preferably 5% to 18% by weight, of the surface treatment agent used relative to the amount of the fumed silica powder that has been heat-treated in step (A).
[0073] The required amount of surface treatment agent may depend on the BET surface area of the fumed silica powder used. Thus, the BET specific surface area of the fumed silica powder subjected to the heat treatment in step (A) is 2 It is preferable to use 0.1 μmol to 100 μmol, more preferably 1 μmol to 50 μmol, and more preferably 3.0 μmol to 20 μmol of the surface treatment agent per unit area.
[0074] In optional step C) of the process of the present invention, the fumed silica powder subjected to heat treatment in step (A) and / or the fumed silica powder obtained in step (B) of the process is crushed or ground to reduce the average particle size of the obtained silica particles.
[0075] The grinding in optional step (C) of the process of the present invention may be achieved by any machine suitable for this purpose, such as a suitable mill.
[0076] However, in most cases, the optional step C) of the method of the present invention is unnecessary or even desirable. Crushing or grinding coarse silica particles usually results in silica particles with a smaller average particle size, but such particles have a relatively broad particle size distribution. Such particles usually contain a relatively large proportion of fines, which makes the handling of these crushed / ground particles complicated. Therefore, the method of the present invention preferably does not include any crushing and / or grinding steps.
[0077] Surface Unmodified Fumed Silica Powder The present invention further provides a surface-unmodified silica powder obtainable by the process of the present invention. The present invention further provides a surface-unmodified silica powder, which can preferably be prepared according to the method of the present invention, having: (a) 1.17 SiOH / nm as measured by reaction with lithium aluminum hydride 2 Less than 0.6SiOH / nm 2 ~1.15SiOH / nm 2 , more preferably 0.6SiOH / nm 2 ~1.14SiOH / nm 2 , more preferably 0.6SiOH / nm 2 ~1.1SiOH / nm 2 , more preferably 0.6SiOH / nm 2 ~1.05SiOH / nm 2 , more preferably 0.6SiOH / nm 2 ~1.05SiOH / nm 2 , more preferably 0.7SiOH / nm 2 ~1.05SiOH / nm 2 , more preferably 0.8SiOH / nm 2 ~1.05SiOH / nm 2 , more preferably 0.9SiOH / nm 2 ~1.05SiOH / nm 2 is the BET surface area d SiOH Number of silanol groups relative to (b) a particle size d measured by static light scattering (SLS) in a 5 wt. % aqueous dispersion of silica after 120 seconds of ultrasonic treatment at 25° C. of 10 μm or less, preferably 5 μm or less, more preferably 3 μm or less, more preferably 2 μm or less, preferably 1 μm or less. 90 The resulting measured particle size distribution reflects a particle size not exceeded by 90% of all particles. 90 Used to define a value.
[0078] The surface-unmodified silica powder of the present invention characterized by the requirements (a) and (b) can be obtained by the method of the present invention described above. The above-mentioned surface-unmodified fumed silica powder is inherently hydrophilic since it has not been surface-treated, i.e., has not been modified by any surface treatment agent. The surface unmodified fumed silica powder according to the present invention preferably has a carbon content of less than 1.0% by weight, preferably less than 0.5% by weight, more preferably less than 0.3% by weight, more preferably less than 0.2% by weight, even more preferably less than 0.1% by weight, and even more preferably less than 0.05% by weight. The carbon content can be determined by elemental analysis according to EN ISO3262-20:2000 (chapter 8).
[0079] The surface unmodified fumed silica powder according to the present invention preferably has a water content of less than 1.0% by weight, more preferably less than 0.7% by weight, more preferably less than 0.5% by weight, more preferably less than 0.4% by weight, more preferably less than 0.3% by weight, more preferably less than 0.2% by weight. The water content can be measured by Karl Fischer titration.
[0080] The surface-unmodified fumed silica powder of the present invention preferably has a methanol wettability of 15% or less by volume of methanol in a methanol / water mixture, more preferably 10% or less by volume, more preferably 5% or less by volume, and particularly preferably about 0% by volume. The methanol wettability of the surface-unmodified fumed silica powder can be measured, for example, as described in detail on pages 5-6 of WO 2011 / 076518.
[0081] The surface-unmodified fumed silica powder according to the present invention has a numerical median particle size d of at most 2 μm, more preferably 0.05 μm to 1.5 μm, more preferably 0.10 μm to 1.2 μm, more preferably 0.15 μm to 1.0 μm, more preferably 0.20 μm to 0.90 μm, more preferably 0.25 μm to 0.80 μm, as measured by static light scattering (SLS) after ultrasonicating a 5 wt. % aqueous dispersion of silica at 25° C. for 120 seconds. 50 The resulting measured particle size distribution is used to determine a median d that reflects a particle size not exceeded by 50% of all particles. 50 is defined as the numerical median particle size.
[0082] The surface-unmodified fumed silica powder of the present invention preferably has a relatively narrow particle size distribution, which is a span of the particle size distribution (d) of less than 7.0, less than 4.0, more preferably 0.8-3.5, more preferably 0.9-3.2, more preferably 1.0-3.1, more preferably 1.0-3.0, more preferably 1.0-2.5, more preferably 1.0-2.0. 90 -d 10 ) / d 50 Such a hydrophilic silica powder having a narrow particle size distribution is preferable because it has particularly good dispersibility in various compositions.
[0083] The surface-unmodified fumed silica powder of the present invention preferably has a tamping density of 300 g / L or less, more preferably 250 g / L or less, more preferably 20 g / L to 250 g / L, more preferably 20 g / L to 200 g / L, more preferably 25 g / L to 180 g / L, more preferably 30 g / L to 150 g / L. The tamping density can be measured in accordance with DIN ISO 787-11:1995.
[0084] The surface unmodified fumed silica powder of the present invention has a surface area of 20 m 2 / g, preferably 20m 2 / g~600m 2 / g, more preferably 30m 2 / g~500m 2 / g, more preferably 40m 2 / g~400m 2 / g, more preferably 50m 2 / g~300m 2 The specific surface area, also referred to simply as the BET surface area, can be determined by nitrogen adsorption according to the Brunauer-Emmett-Teller method in accordance with DIN 9277:2014.
[0085] The surface-unmodified fumed silica powder according to the present invention can be obtained after carrying out step (A) of the method of the present invention, and preferably, the surface-unmodified fumed silica powder according to the present invention is obtained by carrying out step (A) of the method of the present invention.
[0086] Surface Modified Fumed Silica Powder The present invention further provides a surface-modified fumed silica powder obtainable by step (A) and step (B) of the method of the present invention, and preferably, the surface-modified fumed silica powder according to the present invention is obtainable by carrying out step (A) and step (B) of the method of the present invention.
[0087] The present invention further provides a surface modified fumed silica powder having: a) 0.29 SiOH / nm2 measured by reaction with lithium aluminum hydride 2 The BET surface area d SiOH Number of silanol groups relative to b) A 5% by weight dispersion of the surface-treated silica in methanol is ultrasonicated for 120 seconds at 25°C, and the particle size d of 10 μm or less is measured by static light scattering (SLS). 90 .
[0088] Such surface-modified fumed silica powder according to the present invention characterized by requirement (a) and requirement (b) can be obtained by the method of the present invention comprising steps (A) and (B) of the method of the present invention.
[0089] In the present invention, the term "surface modified" is used in the same way as the term "surface treated" and refers to the chemical reaction of a surface-untreated hydrophilic silica with a corresponding surface treatment agent that completely or partially modifies the free silanol groups of the silica.
[0090] The surface treatment agent can be selected from the group consisting of organosilanes, silazanes, acyclic polysiloxanes, cyclic polysiloxanes, and mixtures thereof. Preferably, organosilanes, silazanes, or mixtures thereof are used in the process. Some particularly useful surface treatment agents are the same as those described above with respect to the surface treatment step (B) of the process of the present invention.
[0091] The surface modified fumed silica powder of the present invention can be preferably prepared according to the method of the present invention and has a BET surface area d SiOH The number of silanol groups is 0.45SiOH / nm 2 Less than 0.43SiOH / nm 2 Less than or equal to 0.41SiOH / nm, more preferably 0.41SiOH / nm 2 Less than or equal to 0.39SiOH / nm, more preferably 0.39SiOH / nm 2 Less than or equal to 0.37SiOH / nm 2 Less than or equal to 0.35SiOH / nm 2 Less than or equal to 0.33SiOH / nm, more preferably 0.33SiOH / nm 2 Less than or equal to 0.31SiOH / nm, more preferably 0.31SiOH / nm 2 Less than or equal to 0.29SiOH / nm 2 Less than or equal to 0.28SiOH / nm 2 Less than or equal to 0.25SiOH / nm 2 Less than or equal to 0.20SiOH / nm, more preferably 0.20SiOH / nm 2 Particularly preferably, the surface-modified fumed silica powder of the present invention has a BET surface area d SiOH The number of silanol groups is 0.02SiOH / nm 2 More preferably, it is greater than 0.02SiOH / nm 2 ~0.45SiOH / nm 2 , more preferably 0.03SiOH / nm 2 ~0.40SiOH / nm 2 , more preferably 0.05SiOH / nm 2 ~0.35SiOH / nm 2 , more preferably 0.05SiOH / nm 2 ~0.33SiOH / nm 2 , more preferably 0.05SiOH / nm 2 ~0.30SiOH / nm 2 , more preferably 0.03SiOH / nm 2 ~0.29SiOH / nm 2 , more preferably 0.05SiOH / nm 2 ~0.28SiOH / nm 2 , more preferably 0.05SiOH / nm 2~0.25SiOH / nm 2 , more preferably 0.07SiOH / nm to 0.20SiOH / nm 2 , more preferably 0.10SiOH / nm 2 ~0.20SiOH / nm 2 It is.
[0092] The silanol group density of the surface modified fumed silica powder of the present invention is unprecedentedly low compared to typical surface treated fumed silicas, which gives such silicas unique properties, such as low water content.
[0093] The surface-modified silica powder of the present invention can be hydrophilic or hydrophobic depending on the chemical structure of the surface treatment agent used. Preferably, a surface treatment agent that imparts hydrophobicity is used to produce a surface-treated silica powder having hydrophobicity.
[0094] The term "hydrophobicity" in the context of this specification relates to surface treated silica particles that have a low affinity for polar media such as water. The degree of hydrophobicity of surface treated silica powders can be measured by parameters such as methanol wettability, as detailed for example on pages 5-6 of WO 2011 / 076518. In pure water, the hydrophobic silica completely separates from the water and floats on its surface without being wetted by the solvent. In contrast, in pure methanol, the hydrophobic silica is dispersed throughout the solvent and complete wetting occurs. In the measurement of methanol wettability, the silica sample to be tested is mixed with various methanol / water mixtures and the maximum methanol content at which no wetting of the silica has yet occurred, i.e., 100% of the silica to be tested has been separated from the test mixture, is measured. This methanol content (in volume %) in the methanol / water mixture is referred to as the methanol wettability. The higher the level of such methanol wettability, the more hydrophobic the silica is.
[0095] The surface-modified fumed silica powder of the present invention has a methanol wettability in a methanol / water mixture of more than 20% by volume, more preferably 30% to 90% by volume, more preferably 30% to 80% by volume, particularly preferably 35% to 75% by volume, and most preferably 40% to 70% by volume.
[0096] The surface-modified fumed silica powder of the present invention has a particle size d of 10 μm or less, preferably 5 μm or less, more preferably 3 μm or less, more preferably 2 μm or less, more preferably 1 μm or less, as measured by static light scattering (SLS) after ultrasonicating a 5 wt % dispersion of silica in methanol at 25° C. for 120 seconds. 90 The resulting measured particle size distribution has a value d that reflects the particle size not exceeded by 90% of all particles. 90 Used to define
[0097] The surface-modified fumed silica powder according to the present invention has a numerical median particle size d of at most 2 μm, more preferably 0.05 μm to 1.5 μm, more preferably 0.10 μm to 1.2 μm, more preferably 0.15 μm to 1.0 μm, more preferably 0.20 μm to 0.90 μm, more preferably 0.25 μm to 0.80 μm, as measured by static light scattering (SLS) after ultrasonicating a 5 wt. % dispersion of silica in methanol at 25° C. for 120 seconds. 50 The resulting measured particle size distribution preferably has a median d reflecting a particle size not exceeded by 50% of all particles. 50 is used to define the numerical median particle size. The surface modified fumed silica powder of the present invention preferably has a relatively narrow particle size distribution, which is the span of the particle size distribution (d 90 -d 10 ) / d 50The surface-modified fumed silica powder having such a narrow particle size distribution is preferably characterized by a value of 7.0 or less, more preferably 4.0 or less, more preferably 3.5 or less, preferably 0.7 to 3.5, more preferably 0.8 to 3.5, more preferably 1.0 to 3.2, more preferably 1.1 to 3.1, and more preferably 1.2 to 3.0. The surface-modified fumed silica powder having such a narrow particle size distribution has particularly good dispersibility in various compositions and is therefore preferable.
[0098] The surface-modified fumed silica powder of the present invention has a surface area of 15 m 2 / g, preferably 15m 2 / g~500m 2 / g, more preferably 30m 2 / g~400m 2 / g, more preferably 40m 2 / g~300m 2 / g, more preferably 50m 2 / g~250m 2 / g BET surface area.
[0099] The surface-modified fumed silica powder of the present invention preferably has a tamping density of more than 10 g / L, more preferably 20 g / L to 300 g / L, more preferably 25 g / L to 250 g / L, more preferably 30 g / L to 220 g / L, more preferably 35 g / L to 200 g / L, more preferably 40 g / L to 150 g / L, more preferably 45 g / L to 120 g / L, more preferably 50 g / L to 100 g / L. Tamping density can be measured according to DIN ISO 787-11:1995.
[0100] The surface modified fumed silica powder according to the invention has a carbon content, determined by elemental analysis, of 0.2% to 10% by weight, preferably 0.3% to 7% by weight, more preferably 0.4% to 5% by weight, more preferably 0.5% to 4% by weight, more preferably 0.5% to 3.5% by weight, more preferably 0.5% to 3.2% by weight, more preferably 0.5% to 3.0% by weight, more preferably 0.5% to 2.5% by weight, more preferably 0.5% to 2.0% by weight, more preferably 0.5% to 1.5% by weight. The elemental analysis can be carried out in accordance with EN ISO3262-20:2000 (chapter 8). The sample to be analyzed is weighed into a ceramic crucible, a combustion additive is added and the sample is heated in an induction furnace under a flow of oxygen. The carbon present is oxidized to CO 2 CO 2 The amount of gas is quantified by an infrared detector.
[0101] Particularly preferably, the surface-modified fumed silica powder according to the invention is characterized by a very low carbon content, for example 0.5% to 3.5% by weight, more preferably 0.5% to 3.0% by weight, even 0.5% to 2.0% by weight. However, this is sufficient to achieve extensive surface treatment, for example 30-80% by volume, more preferably 35-75% by volume, more preferably 40-70% by volume of such surface-treated fumed silica in a methanol / water mixture, to achieve a high degree of hydrophobicity. In such surface-treated fumed silica powders, a minimum amount of surface treatment agent is used to achieve the maximum degree of surface treatment, for example the maximum degree of hydrophobicity of the silica powder.
[0102] Particularly preferably, the surface-modified fumed silica powder according to the present invention has a low carbon content, for example, 0.5% to 3.5% by weight, more preferably 0.5% to 3.0% by weight, and even more preferably 0.5% to 2.0% by weight, and a carbon content of, for example, 0.35SiOH / nm 2 Less than or equal to 0.30SiOH / nm, more preferably 0.30SiOH / nm 2 Less than or equal to 0.25SiOH / nm 2 The BET surface area d as follows: SiOHIn this case, the amount of surface treatment agent used can be minimized, thereby minimizing the moisture content of the surface-treated fumed silica.
[0103] The loss on drying (LOD) of the surface-modified fumed silica powder of the present invention is preferably less than 5.0% by weight, more preferably less than 3.0% by weight, more preferably less than 2.0% by weight, more preferably less than 1.0% by weight, more preferably less than 0.8% by weight, more preferably less than 0.5% by weight. The loss on drying can be measured according to ASTM D280-01 (Method A).
[0104] The surface modified fumed silica powder according to the present invention preferably has a water content of less than 0.8% by weight, more preferably less than 0.6% by weight, more preferably less than 0.4% by weight, more preferably less than 0.3% by weight, more preferably less than 0.2% by weight, more preferably less than 0.1% by weight. The water content can be measured by Karl Fischer titration.
[0105] Compositions containing fumed silica powder Another object of the present invention is a composition comprising the surface-unmodified fumed silica powder according to the invention and / or the surface-modified fumed silica powder according to the invention.
[0106] The composition according to the invention can comprise at least one binder. The binder can bind the individual parts of the composition to one another and, if necessary, to one or more fillers and / or other additives, thus improving the mechanical properties of the composition. Such binders can comprise organic or inorganic substances. The binders optionally comprise reactive organic substances. The organic binders can be selected, for example, from the group consisting of (meth)acrylates, alkyd resins, epoxy resins, gum arabic, casein, vegetable oils, polyurethanes, silicone resins, waxes, cellulose adhesives and mixtures thereof. Such organic substances can cause hardening of the composition used, for example by evaporation of the solvent, polymerization, crosslinking reactions or another type of physical or chemical change. Such hardening can take place, for example, thermally or under the action of UV radiation or other radiation. Both single (one) component systems (1-C) and multicomponent systems, in particular two-component systems (2-C), can be applied as binders. Particularly preferred for the present invention are water-based binders or water-miscible (meth)acrylate-based binders and epoxy resins (preferably as a two-component system).
[0107] In addition to or as an alternative to organic binders, the compositions of the present invention may contain inorganic hardening materials. Such inorganic binders, also called mineral binders, perform essentially the same role as organic binders, that is, to bind the additive materials together. Inorganic binders are further classified as non-hydraulic and hydraulic binders. Non-hydraulic binders are water-soluble binders such as calcium lime, dolomitic lime, gypsum and anhydrite that harden only in air. Hydraulic binders are binders that harden in air and in the presence of water and become water-insoluble after hardening. These include hydraulic lime, cement and masonry cement. Mixtures of various inorganic binders may also be used in the compositions of the present invention.
[0108] In addition to or instead of a binder, the composition of the present invention can also contain a matrix polymer, such as a polyolefin resin (e.g., polyethylene or polypropylene), a polyester resin (e.g., polyethylene terephthalate), a polyacrylonitrile resin, a cellulose resin, or a mixture thereof. The fumed silica powder of the present invention can be incorporated into such a matrix polymer or form a coating on its surface.
[0109] Apart from the fumed silica powder and the binder, the composition according to the invention may further contain at least one solvent and / or filler and / or other additives.
[0110] The solvent used in the composition of the present invention can be selected from the group consisting of water, alcohols, aliphatic and aromatic hydrocarbons, ethers, esters, aldehydes, ketones and mixtures thereof. For example, the solvent used can be water, methanol, ethanol, propanol, butanol, pentane, hexane, benzene, toluene, xylene, diethyl ether, methyl tert-butyl ether, ethyl acetate and acetone. Particularly preferably, the solvent used in the heat insulating composition has a boiling point of less than 300 ° C, particularly preferably less than 200 ° C. Such relatively volatile solvents can be easily evaporated or vaporized during the curing of the composition according to the present invention.
[0111] The surface modified fumed silica powder of the present invention is particularly suitable for use in toner compositions.
[0112] Uses of Fumed Silica Powder The surface modification of the present invention and / or the surface modified silica powder of the present invention can be used as a component of paints or coatings, silicones, pharmaceuticals or cosmetics, adhesives or sealants, toner compositions, lithium ion batteries, especially the separators, electrodes and / or electrolytes thereof, as well as to modify the rheological properties of liquid systems, as anti-settling agents, to improve the flowability of powders, and to improve the mechanical or optical properties of silicone compositions. EXAMPLES
[0113] Analysis method BET specific surface area [m 2 / g] was determined by nitrogen adsorption according to the Brunauer-Emmett-Teller method in accordance with DIN 9277:2014. BET surface area d SiOH [SiOH / nm 2 The number of silanol groups relative to the surface area was determined by reaction of a pre-dried sample of silica powder with a lithium aluminum hydride solution as detailed in EP 0 725 037 A1, p. 8, line 17 to p. 9, line 12. This method is also described in Journal of Colloid and Interface Science, Vol. 125, No. 1 (1988), pp. 61-68. The tamped density [g / L] was determined in accordance with DIN ISO 787-11:1995 "General test methods for pigments and extenders - Part 11: Determination of tamped volume and apparent density after tamping". Particle size distribution, i.e. d 10 Value, d 50 Value, d 90 Value and span (d 90 -d 10 ) / d 50 The particle size [μm] was measured by static light scattering (SLS) using a laser diffraction particle size analyzer (HORIBA LA-950) after ultrasonic treatment of a 5 wt % methanol dispersion (for hydrophobic silica powder) or water dispersion (for hydrophilic silica powder) of the surface-treated silica for 120 seconds at 25°C. Methanol wettability [volume % of methanol in methanol / water mixture] was measured according to the method detailed on pages 5-6 of WO 2011 / 076518. The carbon content [wt.%] was determined by elemental analysis according to EN ISO3262-20:2000 (chapter 8). The samples to be analyzed were weighed into ceramic crucibles, added with combustion additives and heated in an induction furnace under a flow of oxygen. The carbon present was oxidized to CO 2 CO 2 The amount of gas is quantified by an infrared detector. The water content [wt %] was measured by Karl Fischer titration using a Karl Fischer titrator.
[0114] Starting materials Starting material 1, BET surface area: 46 m 2 Aerosil® EG50 (manufacturer: Evonik Operations GmbH) with a BET surface area of 282 m / g and tamping density of 117 g / L was used as starting material 2. 2 Aerosil® 300 (manufacturer: Evonik Operations GmbH) with a viscosity of 100 saturation viscosity / g and tamping density of 43 g / L was used.
[0115] Example 1 Starting material 1 was heat treated at 400°C in a rotary kiln with a diameter of about 160 mm and a length of 2 m. The average residence time of the silica in the rotary kiln was 1 h. The rotation speed was set at 5 rpm, so that the throughput of the silica was about 1 kg / h. Dried and filtered compressed air was pumped through a rotary kiln with a length of about 1 m. 3 The air was continuously fed to the kiln outlet (countercurrent to the heat-treated silica flow) at a flow rate of 1000 / hr, and preconditioned air was supplied to the convection in the tubes. The process was smooth. No clogging of the rotary kiln was observed. The physicochemical properties of the obtained heat-treated silica are shown in Table 1.
[0116] Examples 2 to 5 and Comparative Example 1 were carried out in the same manner as Example 1, except that the heat treatment temperature was 700 to 1,300° C. No clogging of the rotary kiln was observed in Examples 2 to 5, but significant clogging was observed in Comparative Example 1. The physicochemical properties of the obtained heat-treated silica are shown in Table 1.
[0117] Comparative Example 2 was carried out by heat treating the starting material 1 in a chamber kiln (manufacturer: Nabertherm). A layer with a bed height of up to 1 cm was heat treated at 1,200° C. for 1 hour. The physicochemical properties of the obtained heat-treated silica are shown in Table 1.
[0118] Example 6 Starting material 2 was heat treated at 400°C in a rotary kiln with a diameter of about 160 mm and a length of 2 m. The average residence time of the silica in the rotary kiln was 1 hour. The process was smooth. No clogging of the rotary kiln was observed. The physicochemical properties of the obtained heat-treated silica are shown in Table 2.
[0119] Examples 7 to 10 and Comparative Example 3 were carried out in the same manner as Example 6, except that the heat treatment temperature was 700 to 1,300° C. No clogging of the rotary kiln was observed in Examples 7 to 10, but significant clogging was observed in Comparative Example 2. The physicochemical properties of the obtained heat-treated silica are shown in Table 2.
[0120] Comparative Example 4 was carried out by heat treating the starting material 2 in a chamber kiln (manufacturer: Nabertherm). A layer with a bed height of up to 1 cm was heat treated at 11,00 ° C for 1 hour. The physicochemical properties of the obtained heat-treated silica are shown in Table 1.
[0121] Example 11 The heat-treated hydrophilic silica obtained in Example 10 (100 g) was surface-treated with hexamethyldisilazane (HMDS). For this purpose, HMDS (8.6 g) was evaporated. The silica powder was heated in a thin layer to 100° C. in a desiccator and then evacuated. The evaporated HMDS was then placed in the desiccator until the pressure rose to 300 mbar. The sample was purged with air and then removed from the desiccator. The surface-treated silica thus obtained had a BET surface area of 190 m 2 / g, carbon content 1.13%, silanol density 0.16SiOH / nm 2 , the methanol wettability in a methanol / water mixture is 45%, and the particle size d measured by static light scattering (SLS) after a 5 wt % dispersion of the surface-treated silica in methanol is sonicated for 120 s at 25 °C. 90 was less than 10 μm.
[0122] Table 1 shows the physicochemical properties of the fumed silica powder obtained by thermal treatment of starting material 1 (BET=46m 2 / g, tamped density = 117 g / L). The BET surface area, tamped density and particle size of starting material 1 do not change significantly in Examples 1 to 5 where the heat treatment is carried out at temperatures up to 1200 °C. Conversely, at a high temperature of 1300 °C (Comparative Example 1), there is a sharp decrease in the BET surface area and the tamped density and particle size (e.g. d 90 The change in BET surface area and particle size was even more pronounced in Comparative Example 2, which was heat-treated at 1200°C but did not migrate the silica during heat treatment. The silanol group density of starting material 1 (2.78 OH / nm 2 ) was significantly decreased in Examples 1-5 and Comparative Example 1, with the largest changes occurring in the range of 400-1000 °C. Interestingly, at a higher temperature of 1300 °C (Comparative Example 1), no further reduction in silanol group density could be achieved.
[0123] Table 2 summarizes the results of the same tests as in Table 1 (Examples 6-10 and Comparative Examples 3 and 4), but for starting material 2 (BET=282 m 2 / g, tamping density = 43g / L), and the results show a similar trend to the results in Table 1. Therefore, by heat treating the hydrophilic fumed silica powder for a certain period of time in the temperature range of 400-1200 °C while moving the fumed silica powder, it was possible to produce silica powder with a relatively small particle size and with almost no change in BET surface area and tamping density. Such heat-treated silica powder is characterized by a particularly low water content. By carrying out such a surface treatment of heat-treated silica without adding water, it is possible to produce a highly hydrophobic silica powder having a particularly low silanol group density and water content (Example 11).
[0124] [Table 1]
[0125] [Table 2]
Claims
1. The BET surface area d of the surface unmodified by any surface treatment agent, measured by reaction with lithium aluminum hydride SiOH The number of silanol groups per nm is at least 1.2 SiOH / nm 2 and the particle size d measured by static light scattering in a 5 wt % aqueous dispersion of silica after 120 seconds of ultrasonic treatment at 25° C. 90 A step (A) of subjecting a surface-untreated fumed silica powder having a particle size of 10 μm or less to a heat treatment at 350° C. to 1,250° C. for 5 minutes to 5 hours. A method for producing a fumed silica powder comprising: The temperature and duration of the heat treatment are SiOH of the thermally untreated and surface untreated fumed silica powders used SiOH is selected to be reduced by 10% to 70% A method wherein the heat treatment is carried out while the fumed silica powder is in motion.
2. 2. The method of claim 1, wherein said silica moves during said heat treating step (A) at a moving speed of at least 1 cm / min.
3. 10. The method of claim 1, wherein no water is added before, during or after step (A).
4. The method of claim 1 , wherein the heat treatment is carried out in a rotary kiln.
5. A step (B) of surface-treating the fumed silica powder obtained in the step (A) with a surface treatment agent selected from the group consisting of organosilanes, silazanes, acyclic polysiloxanes, cyclic polysiloxanes, and mixtures thereof. The method of claim 1 further comprising:
6. 6. The method of claim 5, wherein water is added before, during or after step (B) in an amount of less than 1% by weight of the fumed silica powder used.
7. (a) BET surface area d measured by reaction with lithium aluminum hydride SiOH The number of silanol groups is 1.17 SiOH / nm 2 is as follows: (b) Particle size d measured by static light scattering in a 5 wt % aqueous dispersion of silica after 120 seconds of ultrasonic treatment at 25° C. 90 is 10 μm or less, Surface unmodified fumed silica powder.
8. The silica was subjected to ultrasonic treatment for 120 seconds at 25° C., and the particle size distribution (d 90 -d 10 ) / d 50 The fumed silica powder according to claim 7, wherein the range of
9. 8. The fumed silica powder of claim 7, having a tamped density of 30 g / L to 150 g / L.
10. 8. The fumed silica powder according to claim 7, obtainable by the process according to claim 1.
11. (a) BET surface area d measured by reaction with lithium aluminum hydride SiOH The number of silanol groups is 0.29 SiOH / nm 2 is as follows: (b) Particle size d measured by static light scattering in a 5% by weight dispersion of the silica in methanol after ultrasonic treatment at 25° C. for 120 seconds 90 is 10 μm or less, Surface modified fumed silica powder.
12. 12. The fumed silica powder of claim 11, wherein the carbon content of the surface-modified silica is 0.5% to 3.5% by weight.
13. 12. The fumed silica powder according to claim 11, obtainable by the process according to claim 5 or claim 6.
14. A composition comprising the fumed silica powder of claim 7.
15. 8. Use of the fumed silica powder according to claim 7 in paints or coatings, silicones, pharmaceuticals or cosmetics, adhesives or sealants, toner compositions, as a component of lithium ion batteries, to modify the rheological properties of liquid systems, as an anti-settling agent, to improve the flowability of powders, and to improve the mechanical or optical properties of silicone compositions.